Unlocking the potential of kiwifruit (Actinidia spp.) pot cultivation:A Novel approach for fruit-bearing potted plant production by air layering - Hafeez, A H; Jingyi, Z; Tian, L; Xiaoya, C; Dayong, G; Yunliu, Z (Journal of Horticultural Sciences, 2025)
Kiwifruit potting is used extensively in ornamental plantations. However, the procedure of pot cultivation with fruit-bearing via air layering is still not yet developed. In this study, several treatments were used to induce rooting via air layering, including wounding, hormone use, and environmental conditions. The results showed that both wounding operations such as scraping and girdling, were effectively inducible for rooting in kiwifruit. Application of continued 100 mL ½ Murashige & Skoog (MS) + 0.5 mg/L Indole-3-butyric acid solution every 7 days can significantly enhance the rooting rate by up to 83.33% as compared to plant growth-promoting rhizobacteria, which inhibited rooting. Finally, the rooting canes with fruiting were cut and transferred into the pot, the fruit grew well. Taken together, the developed method provides insight into an efficient way to produce kiwifruit potted plants with fruits in four months that are directly available for commercial sale and scientific research.